ASSESSMENT OF STRATEGIC BUSINESS UNITS IN THE DEVELOPMENT OF TRADITIONAL HEALTH SERVICES INTEGRATION OF ACUPUNCTURE AT TEBET HOSPITAL, DKI JAKARTA PROVINCE, 2020 - Aprilla, Gabe Gusmi (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2021)
Background: The Ministry of Health has trained acupuncture 203 doctors from 160 Government-Owned Hospitals, 1 Army-owned Hospital, 41 Community Health Centers and 1 Health Service Unit owned by the Ministry of Health from 2013 to 2018. One of the hospitals being trained is the Tebet Regional General Hospital and to date have not provided acupuncture services, therefore researcher is interested in analyzing the development of acupuncture services. Methods: This research uses qualitative and quantitative methods. Result: The hospital has characteristics within the average limit because as a class D hospital it is fully accredited and has a vision as a C class hospital. The unavailability of acupuncture services is due to the lack of support from hospital management and the absence of infrastructure. The hospital responds to opportunities within moderate limits and avoids threats within moderate limits such as it makes all visiting patients to be served as long as they have a health insurance card. The results of the Internal External Matrix show that the strategic position of the acupuncture services development business unit is hold and maintain. Recommendation: Efforts to develop acupuncture services require a good marketing strategy to obtain information about competitors and customer needs. Therefore, this strategy will require a lot of new investment in its implementation because it must be preceded by market research.